Sultan Perak, Sultan Nazrin Shah graces the Royal Commissioning Ceremony of the 2024 42nd Public University PALAPES Young Officers - Naqiah, Puaad (UMPSA, 2024)
TANJUNG MALIM, 21 September 2024 - His Royal Highness Paduka Seri Sultan Perak Darul Ridzuan, Sultan Nazrin Muizzuddin Shah Ibni Almarhum Sultan Azlan Muhibbuddin Shah Al-Maghfur-Lah graced the Royal Commissioning Ceremony of the 42nd Public University Reserve Officer Training Unit (ROTU) at Universiti Pendidikan Sultan Idris (UPSI) recently.